(+)-Nootkatone: Progresses in Synthesis, Structural Modifications, Pharmacology and Ecology Uses - Wang, Yu-Bin; Li, Jian-Long; Xu, Fang-Fang; Han, Xiao-Dong; Wu, Yun-Shan; Liu, Bo (Current Chinese Science, 2022)
(+)-Nootkatone is a type of eremophilane naturally derived sesquiterpenoids with a grapefruit smell from plants, widely used in the food and cosmetics industries. Many investigations elucidated that (+)-nootkatone presents extensive pharmacological activity, such as antiproliferation in cancer cells, anti-inflammatory, antioxidant nitration stress, etc. In addition, (+)- nootkatone has been registered by the Environmental Protection Agency as a new active ingredient for use in insecticides and insect repellents against ticks, mosquitoes, and a wide variety of other biting pests. Because of the increasingly stringent environmental supervision and market demand for “natural” (+)-nootkatone, the explorations for producing this high-value chemical by green chemosynthesis and biosynthesis technology are in progress. Structural derivatization is becoming one of the most important ways to exploit pharmaceutical and ecological applications. This review covered the progress of the above research and application advances comprehensively to encourage interested scientists to implement further studies.
Keywords: ecological use